2016
DOI: 10.1108/et-06-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Understanding gender, creativity, and entrepreneurial intentions

Abstract: Purpose – The purpose of this paper is to explore the complex relationships between gender and entrepreneurial intentions. Design/methodology/approach – This paper uses a two study design where the second study is a constructive replication of the first study. The first study uses a cross-sectional design, while the second uses a design where data collection of variables were temporally separated. The analysis is conducted using Hayes (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 58 publications
12
78
0
5
Order By: Relevance
“…Gender significantly affects Entrepreneurial intention having (t-value=7.87 and p-value=0.00) that repudiates with (Smith, Sirdeshmukh, & Combs, 2016) who talked about that gender circuitously affects entrepreneurial intention. Age and education likewise impacts entrepreneurial intention having (t-value=2.28, p-value=0.02 and t-value=2.63, p-value=0.01) separately.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Gender significantly affects Entrepreneurial intention having (t-value=7.87 and p-value=0.00) that repudiates with (Smith, Sirdeshmukh, & Combs, 2016) who talked about that gender circuitously affects entrepreneurial intention. Age and education likewise impacts entrepreneurial intention having (t-value=2.28, p-value=0.02 and t-value=2.63, p-value=0.01) separately.…”
Section: Discussionsupporting
confidence: 53%
“…The outcomes demonstrate that conventional approached are less influenced than the cultural model which is increasingly proper for cross-cultural effects. (Smith, Sirdeshmukh, & Combs, 2016) analyzes the associations between gender, creativity and entrepreneurial intensions. The two-study design has been conducted by using (Hayes, 2013) process of macro.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In this same direction, external barriers to the development of creativity, such as cultural prejudices and social paradigms, are factors that inhibit entrepreneurial intent (Ip, Liang, Wu, Law, & Liu, 2018;Yar et al, 2008). Other research affirms that creativity is an individual capacity that generates greater motivation and intention to undertake in university students (Smith, Sardeshmukh, & Combs, 2016;Zampetakis & Moustakis, 2006). On the other hand, authors, such as Bagheri (2011) and Bagheri, Lope Pihie, & Krauss (2013), have concluded that students at an early age before starting their university studies have high entrepreneurial intent and see less obstacles to developing creative ability.…”
Section: The Barriers Of Creativity In Entrepreneurial Intention In Tmentioning
confidence: 99%
“…According to Robbins and Judge (2013), creativity means combining ideas in unique ways or create continuity between the ideas. Creativity, therefore, is considered a key input for recognizing business ideas (Smith et al, 2016). Creativity is seen as a behavior that generates useful ideas for the development of the organization, and leaders play a vital role in promoting creativity by promoting openness and applying non-traditional and imaginative thinking while solving the problem (Ellen Mathisen et al, 2012).…”
Section: Creativitymentioning
confidence: 99%